A new method of metallurgical silicon purification - Maronchuk, I.E.; Solovyev, O.V.; Khlopyonova, I.A. (Functional Materials, 2005)
Studied have been individual purification stages of metallurgical silicon by recrystallization from the Ga-Si system melt followed by isolation and washing of crystals using chemical methods. The technological sequence for silicon purification has been developed. The method makes it possible to purify silicon containing at least 98.0% Si by weight. The subsequent purification by crystallization from the melt provides the product purity level up to 99.999 mass.% Исследованы отдельные стадии очистки металлургического кремния перекристаллизацией из расплава системы Ga-Si с последующим выделением и промывкой кристаллов химическими методами. Разработана технологическая схема очистки кремния. Способ позволяет очищать кремний с содержанием более 98,0 масс. % Si. При последующей кристаллизационной очистке выращиванием слитка из расплава можно повысить уровень чистоты продукта до 99,999 масс. %. Дослiджено окремi стадiї очищення металургiйного силiцiю перекристалiзацiєю з розплаву системи Ga-Si з наступним видiленням i промиванням кристалiв хiмiчними методами. Розроблено технологiчну схему очищення силiцiю. Спосiб дозволяє очищувати силiцiй з вмiстом бiльш, нiж 98,0 мас. % Si. При наступному кристалiзацiйному очищеннi вирощуванням злитка з розплаву можна пiдвищити рiвень чистоти продукту до 99,999 мас. %.